2014
DOI: 10.1159/000362596
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dirty Neck or Acquired Atopic Hyperpigmentation? An Epidemiological and Clinical Study from the National Skin Centre in Singapore

Abstract: Background: ‘Atopic dirty neck' is a poorly understood acquired hyperpigmentation in patients with atopic dermatitis (AD). Objective: To report a single-centre experience with synthesis of this entity's features. Methods: All patients with AD with dirty neck seen over a 5-month period at the National Skin Centre were invited to participate. Results: Out of 544 AD patients examined, 78 (14.3%) had acquired pigmentation of the neck. The majority had moderate-to-severe underlying eczema. Histopathology showed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
12
1
1
Order By: Relevance
“…in 1987 to describe acquired hyperpigmentation that predominantly affects the anterolateral aspects of the neck in patients with AD. An epidemiological and clinical study of atopic dirty neck from the National Skin Centre in Singapore showed that atopic dirty neck was present in about 14.3% of AD patients and was more common in Asian patients . In comparison, we observed that atopic labial hyperpigmentation was more common in AD than in atopic dirty neck.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…in 1987 to describe acquired hyperpigmentation that predominantly affects the anterolateral aspects of the neck in patients with AD. An epidemiological and clinical study of atopic dirty neck from the National Skin Centre in Singapore showed that atopic dirty neck was present in about 14.3% of AD patients and was more common in Asian patients . In comparison, we observed that atopic labial hyperpigmentation was more common in AD than in atopic dirty neck.…”
Section: Discussioncontrasting
confidence: 50%
“…In comparison, we observed that atopic labial hyperpigmentation was more common in AD than in atopic dirty neck. The pathology is thought to be due to frictional melanosis and post‐inflammatory hyperpigmentation, similar to atopic labial hyperpigmentation …”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the hands is variable and largely depends on the patient's occupation. In some patients, we observe clinical presentations that indicate chronicity, such as dirty neck and vitiligo-like and highly lichenified lesions in the flexural areas [22][23][24]. The association with alopecia areata is, in our experience, an indicator of severe disease.…”
Section: Clinical Patternsmentioning
confidence: 64%
“…Dirty neck, and vitiligo-like lichenified lesions in the flexures are signs of chronicity. [133][134][135] Relapsing ADthis refers to childhood AD with complete resolution before or during adolescence, and recurrence in adulthood; occurs in about 12.2% cases of childhood AD. [131] Adult AD cases are prone to contact hand eczema while few with contact eczema have AD.…”
Section: Clinical Patterns Of Adult Admentioning
confidence: 99%